1995
DOI: 10.2466/pr0.1995.76.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Belief in Lunar Effects on Human Behavior

Abstract: Questionnaires sent to 325 people indicated that 140 people (43%) held the personal belief that lunar phenomena alter individual behavior. Specifically, mental health professionals (social workers, master's clinical psychologists, nurses' aides, LPNs) held this belief more strongly than other occupational groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 10 publications
1
47
0
1
Order By: Relevance
“…Prior studies were confirmed here; there was no clear evidence that lunar cycles had more than marginal (and likely spurious) explanatory power in understanding levels of crime and disorder. Although popular culture, folk lore, and even certain occupational lore suggested the "freaks" come out during full moons (Lieber, 1996;Rotton & Kelly, 1985;Rotton et al, 1986;Vance, 1995), this phenomenon was not reflected in San Antonio police data as used here. Though a small number of associations were noted between lunar phase and various aspects of criminal and disorderly conduct, this was a common element of prior research and could have been a probable effect of the large number of associations under consideration (i.e., a spurious finding).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Prior studies were confirmed here; there was no clear evidence that lunar cycles had more than marginal (and likely spurious) explanatory power in understanding levels of crime and disorder. Although popular culture, folk lore, and even certain occupational lore suggested the "freaks" come out during full moons (Lieber, 1996;Rotton & Kelly, 1985;Rotton et al, 1986;Vance, 1995), this phenomenon was not reflected in San Antonio police data as used here. Though a small number of associations were noted between lunar phase and various aspects of criminal and disorderly conduct, this was a common element of prior research and could have been a probable effect of the large number of associations under consideration (i.e., a spurious finding).…”
Section: Discussionmentioning
confidence: 90%
“…Given that lunar effects are embedded in collective western beliefs (Lieber, 1996;Rotton & Kelly, 1985;Rotton et al, 1986), affects observed in areas heavily influenced by officer discretion (such as the decision to arrest, file an official report, or make referrals) could suffer from social contagion (Purpura, 1979;Simon, 1998). If officers accept that there are lunar effects (Rotton et al, 1986;Vance, 1995) they may opt for differential handling of situations based on lunar phase. In effect, the lunar effect would become a self-fulfilling prophecy; dependent variables would be influenced due to acceptance of the lore, rather than due to actual citizen/offender behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations